2014
DOI: 10.1002/phy2.204
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced obesity alters skeletal muscle fiber types of male but not female mice

Abstract: Skeletal muscles are highly plastic tissues capable dramatic remodeling in response to use, disuse, disease, and other factors. Growing evidence suggests that adipose tissues exert significant effects on the basic fiber‐type composition of skeletal muscles. In the current study, we investigated the long‐term effects of a high‐fat diet and subsequent obesity on the muscle fiber types in C57 BLK/6J mice. Litters of mice were randomly assigned to either a high‐fat diet or a control group at the time of weaning, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
66
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 49 publications
12
66
1
Order By: Relevance
“…A significant increase in genioglossus electromyogram (EMGgg) was found in the postmenopausal group re-examined after hormone therapy2930. Denies and colleagues investigated the long-term effects of a high-fat diet and subsequent obesity on muscle fiber type composition and found that the high-fat diet was associated with a significantly lower proportion of slow, type I fibers in the soleus muscle of male, but not female, mice31. The critical pathophysiological feature of OSAS is sleep-related pharyngeal collapse of the UA, which is partly determined by the properties of different muscle fiber types.…”
Section: Discussionmentioning
confidence: 99%
“…A significant increase in genioglossus electromyogram (EMGgg) was found in the postmenopausal group re-examined after hormone therapy2930. Denies and colleagues investigated the long-term effects of a high-fat diet and subsequent obesity on muscle fiber type composition and found that the high-fat diet was associated with a significantly lower proportion of slow, type I fibers in the soleus muscle of male, but not female, mice31. The critical pathophysiological feature of OSAS is sleep-related pharyngeal collapse of the UA, which is partly determined by the properties of different muscle fiber types.…”
Section: Discussionmentioning
confidence: 99%
“…For example, DNA microarray analysis in skeletal muscle revealed 35 differentially expressed transcripts between male and female rats following a HF diet. 21 Similarly, compared to their male counterparts, female rats elevate mitochondrial content to a lesser extent 20 and do not show changes in fiber type 22 following a HF diet. More importantly, gender-related differences in both apoptosis 69,70 and autophagy 69,71,72 have been noted in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Given that there are fiber/muscle differences in apoptotic 17 as well as autophagic 18,19 signaling and protein expression, a concurrent evaluation of these pathways within skeletal muscles of different fiber composition would provide novel insight regarding this relationship following HF feeding. Additionally, despite evidence that some physiological responses to HF feeding are sex-dependent, [20][21][22] much of the current literature has been conducted using male animals. 10,[23][24][25][26][27][28][29][30][31][32] Recently, calls to eliminate gender bias in animal research have been made; 33,34 making an examination of the muscle-specific adaptations to HF feeding in a female model timely.…”
Section: Introductionmentioning
confidence: 99%
“…Ectopic lipid storage in muscle (i.e., within muscle cells and/or in adipocytes located between muscle fibers) represents a negative risk factor for the development of type 2 diabetes related to muscle insulin resistance (10)(11)(12)(13). Moreover, skeletal muscle of obese subjects also displays an impairment in oxidative capacity (14) and abnormal muscle fiber organization (15,16). An increased amount of VAT in obesity has been proposed to link obesity and muscle metabolic alterations, such as insulin resistance.…”
mentioning
confidence: 99%